Retain Employees from The Influence of Inside and Outside The Local AMDK Company in Jombang - Frianto, Agus (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
This research was conducted to determine the effect of compensation variable significantly on employee turnover intention. This study also wanted to know the effect of work environment on employee turnover intention. And this study tested together the variable compensation and working environment of this study against variable turnover intention. Empirically this research results in a significan influence between variable independent and dependent. Where partially compensated variables have a sig value of 0.00 and a working environment variable with a sig value of 0.011 with a determination value of R2 = 0.532 equivalent to 53.2%. It is described that both variable independent research can explain its relationship with its dependent variables strongly. The value of Fcalculated > Table Ftabel is 41,303 in table 3. At the results of this research the company was asked to be able to provide a large compensation that is tailored to the level of needs of employees in general and the procurement and improving of the facilities and pre-existing in the company's.